Barriers to woman entrepreneurs success: a study in Sabah Women Entreprenuer and Professional Association (SWEPA) / Bibianah Mustafa - Mustafa, Bibianah (2008)
This research examines the demographic profile of women entrepreneur that register with Sabah Women Entrepreneurs and Professionals Association (SWEPA). The research attempts to assess the factors and circumstances that contribute to the low number of women involvement in entrepreneurship in Kota Kinabalu. The main areas that examined namely, the nature and scope of barriers that face by the women entrepreneurs while starting and/or expanding their .business, the factors that facilitated their decision to enter into entrepreneurship and the requirement for special support to facilitate the barriers faced by women entrepreneurs. The research on women entrepreneur barriers among Sabah Women entrepreneur and professional Association members will cover Sabah women entrepreneurs and professional association (SWEPA) range from selfemployed business to the business that involves the high usage of technology in providing commodities or services. The targets not only for those already succeed but also those that just started to build their endeavor.